MENINGKATKAN PROFESIONAL GURU DALAM MENERAPKAN PEMBELAJARAN SAINTIFIK MELALUI WORKSHOP - Armanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
The aim of this study is to improve teacher competence in applied of Scientific Learning Approach through workshop and in SMP Negeri 1 Sunggal. The method of this study is school Action Research by using 2 cycles where each cycle consists of: (1) planning, (2) actuating and observation, (3) evaluating and (4) reflecting. The Subjects of this study are the teachers who teach in SMP Negeri 2 Sunggal Deli Serdang. They are 34 teachers. The technique of collecting data is observation, interview, questioner, and study of documentation. The technique of analising daa is by using the calculating of the percentage of the teachers who are able to apply Scientific Learning Approach and the persentage of the teacher who can not apply cntextual teaching and learning Approach in class,The results of the study show: (1) There is the increasing of the amount of the teachers who apply Scientific Learning Approach, from 34 teachers, it is still 24 ( 70,59%) of tachers who apply Scientific Learning Approach in first cycle and then it is improve in second cycle tobe 30 (88,24%) teachers who are able to apply Scientific Learning in class. (2) There is the decreasing of the amount of the teachers who are not able to apply Scientific Learning Approach, from 34 teachers, it is still 10 ( 29,41%) of tachers who can not apply Scientific Learning Approach in first cycle and then in second cycle is tobe 4 (11,76%) teachers who are not able to apply Scientific Learning in class (3) The competence of teachers in applying contextual teaching and earning can be improved through workshop..